ARSENIC RESISTANT BACTERIA ISOLATED FROM CONTAMINATED SOIL AND SELECTION OF ARSENIC REDUCING STRAINS - APARAJITA MAJUMDER (The Bioscan, 2012)
Arsenic (As) is one of the most toxic pollutants in the environment. Continuous use of contaminated ground water for irrigation made the soil secondary source of As. Present study was aimed to investigate if bacteria present in contaminated soil can convert immobilized arsenate (AsV) to mobile arsenite (AsIII) and having a potential role to increase As pollution in the environments or not. Thirty five As resistant bacteria were isolated by an enrichment culture method from As contaminated soil in which14 bacterial strains having the resistance capacity of 250-500mgL-1 in case of AsIII and 8000-12000mgL-1 in case of AsV. Highest resistant capacities showed by the bacterial isolates ArB-15, it could resist upto 12000mgL-1 (160 mM) of AsV and 500mgL-1 (6.66 mM) of AsIII in culture media. Five arsenic reducing bacterial isolates (ArB-08, ArB-15, ArB -22, ArB-28 and ArB- 31) were screened and they were identified by their morphological and biochemical characteristics. This isolates may have potential role in As dissemination in the environments.